APPLICATION OF REMOTE SENSING IN MANGROVE STUDIES : A LITERATURE REVIEW - Zainul Hidayah (Jurnal Kelautan, 2010)
In order to assess the extent of the decline of mangrove ecosystems, extensive mapping and monitoring programs are needed. To monitor the change in large-scale coverage of mangrove areas over certain periods of time, remote sensing technology offers many advantages compared to conventional field monitoring. The main benefit of using remote sensing is related to its speed and continuity in collecting space images of a broad area of the Earth’s surface. With the specific application on mangrove studies, remote sensing enables spatial and spectral information to be collected from the mangrove forests environment mostly located in inaccessible areas, where ground measurements become difficult and expensive. This review of the literature emphasizes the application of remote sensing in change detection and mapping of mangrove ecosystems. Key words : mangroves, remote sensing, mapping, field monitoring, continuity